Localization in Humanitarian Response: Strengthening Local Communities Capacity Through Women's Leadership in Disaster Risk Reduction (Case Study: Central Sulawesi and Banten Province) - Imaduddin, Riza; Syapitri, Richa (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2022)
The impact of humanitarian crises and disasters on structural inequalities and women'svulnerability is discussed in depth in this paper. Despite these difficulties, women are still the earliestresponders in disasters, have the ability to reach hard-to-reach areas, and have a great awareness of the localcontext. The findings of research and lessons learned from the YAA program in humanitarian response inCentral Sulawesi and Banten will be the focus of this paper. There are five important results of the researchand learning program. First, the disaster increased pre-existing gender disparities. This crisis has affectedwomen and girls disproportionately. For women, this has resulted in new risks and vulnerabilities, as wellas new potential for change. Secondly, men continue to dominate the official decision-making structuresand coordinating systems for disaster response. Women and women-led organizations, on the other side,have been able to impact informal and local decision-making spaces. The third finding is that women andwomen-led groups have a wide range of skills, expertise, and connections that become important assets inhumanitarian assistance. Due to a lack of competence in humanitarian work and operational capacity issues,women's participation is still limited. The fourth result is that local community voices, knowledge, andcultural traditions can all be deployed as resources in a community-based disaster risk reduction programthat is integrated into regional development policy. The last result is that the community's collective memoryof disasters, as well as local understanding about disaster risk mitigation, must be transferred down throughthe family in order for potential disasters to be dealt with effectively. In other words, localization inhumanitarian response brings communities, particularly local women, at the centre of humanitarianpreparedness and response in a fair and dignified manner. It is believed that by localizing humanitarianresponse, local capacity will increase, reducing disaster risk and promote community resilience in the faceof disasters.